IMPLEMENTASI PERATURAN UNDANG-UNDANG NOMOR 3 TAHUN 2024 TENTANG PENAMBAHAN MASA JABATAN KEPALA DESA DI KABUPATEN SUMBAWA (Studi di Desa Langam Kecamatan Lopok Kabupaten Sumbawa) - Gustina, Serlina; Supriani, Desta; Yuliyanti, Putri Eka; Supriadi, Dedi (Jurnal Ekonomi & Bisnis, 2025)
This study aims to examine the implementation of Law Number 3 of 2024 concerning the additional term of office of Village Chief in Sumbawa District, specifically in Langam Village. The regulation extends the term of office of Village Chief from six years to eight years, with a maximum limit of two terms. This policy aims to improve the stability of village development and the effectiveness of governance. The type of this study was descriptive study with a qualitative approach. The data used in this study were obtained directly using interview techniques to describe the policy implementation process in the field. The data sources consist of Village Chief and several community and traditional leaders. The collected data was analyzed using qualitative data analysis techniques developed by Miles and Huberman, including data reduction, data presentation, and drawing conclusions or verification. The results of the study showed that although the extension of the term of office has the potential to strengthen the continuity of development programs and community social relations, it also presents challenges such as the potential for authoritarianism, democratic stagnation, and obstacles to village leadership regeneration. These findings provide an important picture for better policy making in managing village government reform in the future.